Bahasa Gaul “Jaksel” Sebagai Eksistensi Di Kalangan Remaja Jakarta - Balqis, Haura Asqo; Anggoro, Sheryl Delvina Aurora; Irawatie, Aniek (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Language is used as a means of communication between individuals with each other, both orally and in writing. The alteration causes an increase in the type of language over time and gives rise to many new languages. As of now, there is a dominant language in society, namely slang. Slang itself has existed for a long time, known as program language. Slang is a non-standard language, this language is usually used by teenagers when they communicate. One example of this slang is the slang "Jaksel" which is very popular among young people in Jakarta, especially teenagers in South Jakarta. Because the use of "Jaksel" slang is very widespread among Jakartan teenagers, therefore the purpose of this study is to find out "Jaksel" slang existence among Jakartan teenagers. This study uses a qualitative descriptive method with interview techniques proposed to youth sources in Jakarta. The results showed that South Jakarta slang is seen in the existence of Jakarta teenagers because this language is a unique language with a mixture of Indonesian and English and is widespread in social media circles. Thus, South Korean slang is considered something that exists in Indonesia. among young people in Jakarta because of the impact of social media which causes the language to become a trend.